Integrasi Nilai-Nilai Al-Qur'an dan Hadits dalam Pendidikan untuk Membangun Tanggung Jawab Konservasi Alam di Madrasah Ibtidaiyah Ihyaul Islam Pakuniran - Wulidatul Habibah; Ainur Rofiq Sofa; Abd. Aziz; Imam Bukhori; Muhammad Hifdil Islam (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Environmental degradation caused by excessive exploitation and natural damage has become increasingly concerning in the modern era. To address this issue, madrasahs, as Islamic educational institutions, play a crucial role in instilling environmental conservation values based on the teachings of the Qur'an and Hadith. This study aims to explore the Qur'an and Hadith-based educational approach implemented at Madrasah Ibtidaiyah Ihyaul Islam Pakuniran in fostering students' awareness of their responsibilities toward environmental conservation. The study employs a qualitative method with a descriptive approach, aiming to deeply understand the teaching processes and the application of environmental education. Data were collected through interviews with the headmaster, teachers, and students, complemented by classroom observations and analysis of curriculum documents and teaching materials. Data validity was strengthened using triangulation to ensure the accuracy and reliability of the findings. The results show that integrating the teachings of the Qur'an and Hadith, such as the concept of maintaining environmental balance (mizan) and the prohibition of environmental destruction (fasad), successfully enhanced students' awareness of the importance of environmental preservation. Activities such as tree planting and waste management, in which students actively participate, reinforced their sense of responsibility toward environmental sustainability. This study concludes that the Qur'an and Hadith-based educational approach holds significant potential in shaping environmentally conscious generations capable of fulfilling their role as guardians of nature in accordance with Islamic teachings.